HUMAN AND SOCIAL CAPITAL IN PLATFORM-BASED FREELANCING: THE MEDIATING ROLE OF DIGITAL ENGAGEMENT IN FREELANCE SUCCESS - Sattayathamrongthian, Mahachai; Makerd, Pawaris (RMUTT Global Business and Economics Review, 2026)
The rapid expansion of global digital labor platforms has increased opportunities for Thai freelancers to access cross-border work. However, success in algorithmically governed labor markets depends on more than technical competence alone. It involves the interplay of individual capabilities, relational networks, and platform-based engagement behaviors. This quantitative study develops and tests a structural model examining the effects of human capital, social capital, and digital engagement on freelance success. Data were collected from 459 Thai freelancers with verified cross-border experience and analyzed using Structural Equation Modeling (SEM). Research results indicate that human capital has significant direct effects on social capital, digital engagement, and freelance success. Social capital emerges as the strongest predictor of freelance success and positively influences digital engagement. Bootstrap mediation analysis confirms that both social capital and digital engagement transmit the effects of human capital to career outcomes. Research findings suggest that freelance success in platform economies is shaped by the interaction between competence, network embeddedness, and digital engagement behaviors. These results provide empirical evidence from an emerging economy context and offer implications for strengthening workforce capability development in global digital labor markets.